2016
DOI: 10.1016/s2352-3018(15)00231-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, bone and metabolic effects of HIV nucleoside reverse transcriptase inhibitor BMS-986001 (AI467003): a phase 2b randomised, controlled, partly blinded trial

Abstract: MethodsAI467003 was a Phase 2b, randomised, active-controlled, blinded-to-BMS-986001 dose trial.HIV-1-infected adults with plasma HIV-1 RNA greater than 5000 copies per mL and CD4+ T-cell counts greater than 200 cells/mm 3 were randomised 2:2:2:3 to three BMS-986001 arms (100, 200 or 400 mg once daily), or reference arm (TDF 300 mg once daily), each with efavirenz (600 mg once daily) and lamivudine (300 mg once daily). Both subjects and investigators remained blinded to BMS-986001 dose, but not allocation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Ultimately, we included 25 distinct papers for final data extraction (Figure 1). Of these, 10 investigated PrEP users [1,3,11,12,1520] and were included in our primary analyses, while 15 investigated HIV [2135]. We did not find any HBV studies or new relevant conference proceedings that had not already been published as one of our reviewed studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, we included 25 distinct papers for final data extraction (Figure 1). Of these, 10 investigated PrEP users [1,3,11,12,1520] and were included in our primary analyses, while 15 investigated HIV [2135]. We did not find any HBV studies or new relevant conference proceedings that had not already been published as one of our reviewed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [23,24,2628,3134] measured BMD changes over 1 year in people using TDF for HIV. As for the PrEP studies, all showed a larger decrease from baseline in TDF compared with non-TDF treated participants.…”
Section: Resultsmentioning
confidence: 99%
“…Although d4T itself is being phased out as a treatment for HIV, chemically modified versions of d4T may yet find a place in the future. A 4′‐ethynyl derivative of d4T (BMS‐986001) in Phase 2 trials showed similar efficacy as tenofovir disoproxil fumarate; however, development was discontinued due to a lower resistance barrier and gains in both peripheral and central fat accumulation . Such modifications could add specificity while retaining the flat ring that may allow d4TTP to retain the same catalytic efficiency as dTTP, despite the absence of the 2′ hydroxyl.…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing phase 2a study is evaluating the safety and tolerability of TPN-101 on a small sample (40 participants) of C9orf72 ALS/FTD patients (NCT04993755). TPN-101 (OBP-601, BMS-986001, festinavir, censavudine;Smith et al, 2015) is a thymidine analog NRTI (nucleoside reverse transcriptase inhibitor) that shows major efficacy against HIV-2 and HIV-1 (Gupta et al, 2016). The active form of TPN-101 (BMS-986001-5 -triphosphate) is a substrate for incorporation by HIV-1 reverse transcriptase, inducing the termination of viral DNA synthesis (Smith et al, 2015).…”
Section: Tpn-101mentioning
confidence: 99%